The Process of Accommodation and Integration of New Talents in the Angolan Public Organizations, Politécnico Institute of The Cuito Cuanavale University (Global Journal of Human-Social Science, 2023)
the company s Human Resources department has this responsibility to make this possible However the overall objective is to analyze the process of hosting and integrating new talent in Dinefu Events Service and Trade And how many specific objectives is to present the methods of the process of welcoming and integrating new talent into organizations Describe the methods of the process of welcoming and integrating new talent into organizations and Describe the perception of managers and employees about the importance of the process of welcoming and integrating new talent into organizations The methodology used to perform the work is exploratory-descriptive and qualitative-quantitative For the results obtained the interview with the 20 employees of the company IP-UCC Of which 11 corresponded to 55 stated that they have knowledge of the process of reception and integration and that corresponds to 45 affirmed that the method used provides a planned and careful integration in short we can affirm that the obtained results are satisfactory and were reached
Keywords: reception; integration; manual of reception; socialization and culture